Respuesta :

Answer:

Step-by-step explanation:

a) Input = -9   ⇒ x = -9

y = x² + 3

Plugin x = (-9),

y = (-9)² + 3  

  =  81 +  3                {(-9)² = -9 * (-9) = 81}

y = 84    ---> Output

y = √x - 2

  = √-9 - 2          { i² = -1}

  [tex]= \sqrt{3*3 * i^{2}}-2\\\\=3i -2[/tex]    

y = 3i - 2  ------> Output

b) Output = 0

y  = x² + 3

x² + 3 = 0

x² = -3

[tex]x = \sqrt{-3}=\sqrt{3i^{2}}\\\\x = i \sqrt{3}[/tex]

y = √x -2

0 = √x - 2

√x = 2

Take square,

[tex](\sqrt{x})^{2}=2^{2}\\\x = 4[/tex]